1991
DOI: 10.1021/bi00242a022
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a human recombinant T-cell protein-tyrosine-phosphatase from a baculovirus expression system

Abstract: A 48-kDa human T-cell protein-tyrosine-phosphatase (TC.PTPase) and a truncated form missing an 11-kDa C-terminal segment (TC delta C11.PTPase) were expressed by using the baculovirus system and characterized after extensive purification. The full-length PTPase was restricted to the particulate fraction of the cells from which it could be released by a combination of salt and detergent. The enzyme was entirely specific for phosphotyrosine residues. It displayed a low level of activity toward phosphorylated, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 37 publications
(39 reference statements)
5
39
0
Order By: Relevance
“…In the above-mentioned publication it was also observed that the activity of the T-cell PTPase against phosphorylated RCML is suppressed by the C-terminus (Zander et al, 1991). Although the differences are modest, our data suggest that the C-terminus of PTPlB also exerts an inhibitory influence on the activity.…”
Section: Discussionsupporting
confidence: 62%
“…In the above-mentioned publication it was also observed that the activity of the T-cell PTPase against phosphorylated RCML is suppressed by the C-terminus (Zander et al, 1991). Although the differences are modest, our data suggest that the C-terminus of PTPlB also exerts an inhibitory influence on the activity.…”
Section: Discussionsupporting
confidence: 62%
“…8A). PTP1B and TCPTP, which display comparable specific activities in assays in vitro (55,62), were overexpressed in the p210 bcr-abl transfectants (Fig. 8C and D).…”
Section: Resultsmentioning
confidence: 90%
“…The nature of the subcellular localization of the T-cell PTPb has yet to be clarified. However, both rat PTPase 1 and the human placental PTPase 1B are targeted to the endoplasmic reticulum (10,37 (7), since no basic cluster separated by the consensus 10-amino-acid spacer region exists in the carboxyl-terminal region between amino acids 345 and 369. The results of these experiments indicate that the MPTP NLS resembles the NLS motifs present in simian virus 40 large T antigen (7,29) and in the nucleolus-localized human immunodeficiency virus Tat protein (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although isolated from a human T-cell cDNA library, this enzyme is ubiquitously expressed in human tissues. In vitro expression of the cDNA yields an inactive enzyme that can be activated by trypsin cleavage of a hydrophobic carboxyl terminus (37). This stretch of hydrophobic amino acids is thought to anchor the enzyme to high-molecular-weight complexes from which it can be released and activated by proteolytic processing.…”
mentioning
confidence: 99%